Trends and Prospects in Educational Modernisation: A Hermeneutic Approach - A. F. Zakirova; Ye. N. Volodina (Russian State Vocational Pedagogical University, 2018)
Introduction. For over two decades, Russian education has been in a state of permanent reform. Due to the long and unproductive nature of the modernisation process, researchers are paying special attention to systemic factors, noting that system optimisation processes are structured primarily around organisational and technological models derived from industry. The prevalence of the technological component over the axiological results in the consolidation of a pragmatic, narrowly functional, technocratic vector of education development. To overcome this situation and to break this deadlock, a profound reconsideration of the values underlying mechanisms of reform is required, taking into account multifaceted personal, social, national and universal relations, as well as unity of content, forms and means of education.The aims of the research were identified as follows: to analyse the current trends of modernisation in comprehensive schools and higher educational establishments; to justify humanistic mechanisms for improving the modernisation in the context of language education, which performs personally developing and socialising functions under ideological pluralism and opposition of value systems.Methodology and research methods. The research was conducted taking a person-activity-based approach, referring to cultural-historical concepts, ideas of philosophical hermeneutics and traditional principles of pedagogical methodology. The theoretical framework was based on the publications and philosophical foundations of Russian and foreign scholars, who define the key role of humanistic principles and value orientations in education. The following standard research methods were used: comparison, induction, deduction, abstraction, synthesis, specification, structural and logical modelling, content analysis of documents and scientific publications on the stated problem, observation, questioning, peer review and experiment. In addition, non-standard methods and research techniques such as metaphorical modelling, biographical method and interpretational techniques were used.Results and scientific novelty. Modernisation processes in Russian education were considered: regulatory base, purposes, priorities, problems and prospects. The following thesis was proposed: at the new stage of socio-historical transformation, it is necessary to overcome the negative effects of long-term practice in the reform of the national educational system through developing established traditions as well as updating the humanistic potential of education and ensuring its axiological enrichment. The authors consider pedagogical hermeneutics as a potentially productive means and methodological tool. Pedagogical hermeneutics implies a heuristic and poly-variable apperception of reality through education in order to understand and interpret different genres of cultural texts, providing simultaneous support both to the general public and to the individual, on the basis of rational and emotionally intelligent experience accumulated in science, religion, art, language and national traditions - i.e. culture as a whole. It was shown that language education based on principles of pedagogical hermeneutics is capable of establishing humanistic mechanisms of personactivity-based social norms and cultural models. The authors presented a number of modelling options for the realisation of the proposed hermeneutical approach: various experimentally-validated techniques, educational approaches and procedures designed by teacher-researchers were briefly described, focusing on the achievement of qualitative conformance of educational results to the humanistic appeals and urgent needs of society.Practical significance. The use of hermeneutical techniques as educational tools and procedures allows us to decode semiotic information of curricula subjects; in addition, when using meta-language, it is possible to expand the content by adding personal value-sense and dialogical subjectivity, as well as to transform it into a personal sign-symbol or behavioural template. The acquisition of language experience in the process of humanistic-centred education increases the immunity of a student to various manifestations of character defectivity, strengthening identity and resistance to manipulation of consciousness in political and ideological processes and mass media. Moreover, language experience resists the deformation of the communicative sphere and verbal-cognitive processes, encouraging personal self-realisation.